Mikroba Kontaminan Pada Biji Pala di Pulau Nusalaut: Karakteristik Morfologi, Frekuensi Keberadaan dan Estimasi Kuantitatif - Costanza Uruilal; Jogeneis Patty (Proceedings Series on Physical & Formal Sciences, 2022)
Research objectives: 1) Identify internal factors (strengths-weaknesses) and external (opportunities-threats) that affect the home marketing mix of coconut sugar industry in Jeruklegi District. 2) Analyzing alternative marketing mix strategies for the coconut sugar home industry in Jeruklegi District. 3) Analyzing the best marketing mix strategies that are priorities to be applied to the coconut sugar home industry in Jeruklegi District. The method used is a descriptive method with the research location in Jeruklegi District which was determined intentionally (Purposive Sampling) with certain selection considerations. Involving 25 respondents of coconut sugar craftsmen. The formulation of the home marketing mix strategy for the coconut sugar industry was analyzed by SWOT (Strengths, Weaknesses, Opportunities, Threats). (Rangkuti, 2006). The results showed that internal factors were the availability of coconut trees, coconut sugar production activities were carried out continuously, the location of the coconut sugar processing business was quite strategic, the price of coconut sugar products was able to compete, the availability of experienced workers in the coconut sugar processing business, ownership of business capital. craftsmen independently, limited number of coconut trees, product quality does not yet have uniformity (taste, color and shape), lack of marketing information sources, level of production and packaging technology is still traditional, limited working capital of craftsmen, craftsmen have not done bookkeeping management and there is no group / cooperative. The position of the coconut sugar home industry in the Jeruklegi District, Cilacap Regency is in the Aggressive Region with the main strategy being the SO strategy, namely 1) Optimizing geographical conditions that support the agroclimate of natural resources and human resources of craftsmen in producing coconut sugar products continuously with competitive prices for coconut sugar products, 2) Optimizing production activities continuously in order to capture high market share opportunities both domestically and internationally with competitive prices as substitute products through partnership relationships between coconut sugar producers.